Translation efficiencies of the 5′ untranslated region from representatives of the six major genotypes of hepatitis C virus using a novel bicistronic reporter assay system - Collier, Adam J.; Tang, Shixing; Elliott, Richard M. (Journal of General Virology, 1998)
The 5′ untranslated region (5′UTR) of hepatitis C virus (HCV) contains an internal ribosome entry site (IRES) which directs translation of the viral open reading frame (ORF). The 5′UTR is highly conserved between virus isolates in both primary sequence and predicted secondary structure. We cloned and sequenced the 5′ regions (nt 18 of the 5′UTRto nt 15 of the core coding sequence) of HCV isolates representing the six major genotypes and subcloned these into a bicistronic, dual luciferase reporter construct. The relative expression of the two luciferases, one directed by the HCV IRES and the other by cap-dependent ribosome scanning, was used to compare the activities of the different IRES elements in transfected cells. The 5′UTR from a genotype 2b isolate was the most efficient at directing translation in all four cell lines tested: BHK-21, HeLa-T4 , HuH7 and HepG2. In HepG2 cells the 2b 5′UTR was three times as efficient as the type 6a 5′UTR, which was generally the least active IRES tested. These data suggest that HCV isolates are not able to translate their ORF with equal efficiency, and provide a starting point from which further sequence-function studies can be undertaken.